Neurodegenerative and neuroinflammatory changes in SOD1-ALS patients receiving tofersen - Cecilia Simonini; Elisabetta Zucchi; Ilaria Martinelli; Giulia Gianferrari; Christian Lunetta; Gianni Sorarù; Francesca Trojsi; Roberta Pepe; Rachele Piras; Matteo Giacchino; Federico Banchelli; Jessica Mandrioli (Scientific Reports)
Abstract The initiation of tofersen, a new specific antisense oligonucleotide (ASO) for SOD1 pathology, marked a significant turning point for SOD1-ALS patients. While clinical trials and early access program studies reported a significant reduction in plasma and cerebrospinal fluid (CSF) neurofilament levels, neuroinflammation following prolonged treatment was never assessed. In this multicenter study, we evaluated a cohort of 18 SOD1-ALS patients treated with tofersen, analyzing correlations between biomarkers of neurodegeneration/neuroinflammation and clinical variables indicative of disease progression. NfL, NfH, CHI3L1, and Serpina1 levels in serum and CSF were determined by semi-automated immunoassays (Ella™ technology). Generalized linear mixed models were employed to investigate longitudinal trends of these biomarkers. Our data highlighted a progressive decrease in CSF neurofilament levels during tofersen treatment (MR = 0.97, 95% CI 0.94–0.99, p = 0.006 and MR = 0.98, 95% CI 0.95–1.00, p = 0.076 for NfL and NfH in CSF, respectively). Conversely, CSF levels of SerpinA1 and CHI3L1 increased over time (MR = 1.12, 95% CI 1.08–1.16, p < 0.0001 and MR = 1.039, 95% CI 1.015–1.062, p = 0.001 for SerpinA1 and CHI3L1 in CSF, respectively), but these modifications were most apparent after six and twelve months of therapy, respectively. Disease progression rate did not correlate with these biomarker trends. We observed a significant decrease in neurofilament levels during Tofersen treatment, alongside an increase in neuroinflammatory markers, potentially linked to an immune response triggered by ASO treatment. Given the limited data on tofersen’s long-term efficacy in ALS due to its recent introduction, identifying biomarkers that predict clinical outcomes such as diminished therapeutic response or adverse effects is crucial. These biomarkers may help to better understand the underlying pathomechanisms of ALS and tofersen’s role in modulating disease progression.